Terminological note: There isn't really such a thing as an 'inductive definition'. Rather, what you are trying to do is to come up with a recursive definition.
However, once such a recursive definition is in place, you can use structural induction to prove things about it.
For example, using the recursive definition as given by @Taroccoesbrocco, we can now prove by structural induction that $\varphi^* \Leftrightarrow \neg \varphi$ (I wouldn't say $\varphi^* = \neg \varphi$, since within the context of metalogic the '$=$' is used to indicate that the two formulas are syntactically/symbolically the same symbol string, whereas of course you just want to prove logical equivalence, for which we use $\Leftrightarrow$)
OK, so here goes that proof:
Base: $\varphi$ is atomic. Then by definition, $\varphi^* = \neg \varphi$
Step: There are three cases to consider:
Suppose $\varphi = \neg \varphi_1$. By inductive hypothesis we can assume $\varphi_1^* \Leftrightarrow \neg \varphi_1$. But that means that $\varphi^* = (\neg \varphi_1)^* = \neg \varphi_1* \Leftrightarrow \neg \neg \varphi_1 = \neg \varphi$
Suppose $\varphi = \varphi_1 \land \varphi_2$. By inductive hypothesis we can assume $\varphi_1^* \Leftrightarrow \neg \varphi_1$ and $\varphi_2^* \Leftrightarrow \neg \varphi_2$. Hence: $\varphi^* = (\varphi_1 \land \varphi_2)^* = \varphi_1^* \lor \varphi_2^* \Leftrightarrow \neg \varphi_1 \lor \neg \varphi_2 \Leftrightarrow \neg (\varphi_1 \land \varphi_2) = \neg \varphi $
Suppose $\varphi = \varphi_1 \lor \varphi_2$. By inductive hypothesis we can assume $\varphi_1^* \Leftrightarrow \neg \varphi_1$ and $\varphi_2^* \Leftrightarrow \neg \varphi_2$. Hence: $\varphi^* = (\varphi_1 \lor \varphi_2)^* = \varphi_1^* \land \varphi_2^* \Leftrightarrow \neg \varphi_1 \land \neg \varphi_2 \Leftrightarrow \neg (\varphi_1 \lor \varphi_2) = \neg \varphi $